THE PURPOSE AND TASKS OF DEVELOPING SMALL BUSINESS AND ENTREPRENEURIAL ACTIVITIES: THE CASE OF NAVOIY REGION - Elov Olimdjon Komilovich; Sabina Buriboyeva (Modern American Journals, 2025)
In this article, the key purposes and tasks of developing small business and entrepreneurial activities are analyzed using the example of the Navoiy region. The importance of measures to support, promote, and develop small businesses and private entrepreneurship in the context of ongoing economic reforms in Uzbekistan is discussed, along with ways to introduce innovative approaches into various sectors of the economy. The article examines the existing potential, regional characteristics, as well as the prospects and challenges of further developing small business and private entrepreneurship in the Navoiy region. Based on the analysis, scientifically grounded proposals and practical recommendations are provided to further improve small business and entrepreneurial activities.
Keywords: Small business, entrepreneurial activity and entrepreneurship, Navoiy region, economic reforms, financial support, innovative development.